Pembelajaran Modul Fisika Berbasis Inkuiri di Masa Pandemi di Kelas XI SMA Negeri 1 Tinombo - Saraswati Saraswati; Amiruddin Hatibe (JPFT (Jurnal Pendidikan Fisika Tadulako Online), 2023)
This research aims to find out: (1) students' interest in learning with inquiry-based modules during the pandemic, (2) the effect of inquiry-based physics modules on student learning outcomes. This type of research is descriptive research obtained by using a combination approach. The population of this study were all students of class XI MIPA SMA Negeri 1 Tinombo. The sample in this study were 34 students of class XI MIPA 3 as many as 34 students. The instruments used to collect data in this study include learning outcomes tests and interest questionnaires. The learning outcomes test obtained showed that the posttest average score was 22,21, which was higher than the pretest average score, which was 5,94. Hypothesis testing (t-test) obtained the value of tcount > ttable or 21.36 > 2.034 at the level of significance = 0.05. This means that the value of tcount is outside the H0 acceptance area. The data obtained from the N-Gain test, namely the average value of the N-Gain percentage of 0.5 is included in the moderate criteria because it meets the N-Gain percentage > 0.3. The results of the interest questionnaire data analysis showed that the percentage of interest of all students was 86.42% who were in the very interested category. Therefore, it can be concluded that students' interest in learning is very good and there is an effect of using an inquiry-based module on learning outcomes.